Remains of Zygolophodon turicensis (Proboscidea, Mammutidae) from the coal mines near Bitola, Republic of Macedonia - Risto Garevski; Biljana Garevska; Georgi N. Markov (Historia naturalis bulgarica, 2012)
We report Zygolophodon turicensis (Schinz, 1824) from the Miocene deposits in a coal mine near Bitola, Republic of Macedonia, and refer a misidentified molar from Nerezi near Skopje published in the 1930s to the same species. Zygolophodon turicensis is a new taxon to the fossil fauna of Macedonia, and the finds discussed in the paper are among the few fossils of pre-Turolian age from the country.